Electroencephalographic response to intravenous diazepam during status epilepticus - MİDİ, İPEK; AĞAN YILDIRIM, KADRİYE (UNIVERSITATSVERLAG ULM GMBH, 2011)
To determine the electroencephalographic (EEG) response to intravenous bolus administration of diazepam during status epilepticus (SE), we retrospectively evaluated the time to the disappearance of epileptiform activity in EEG recordings after 10 mg intravenous bolus administration of diazepam, and examined the relationship of this response time to the duration, etiology, and outcome of SE. Patients with SE who responded positively to diazepam administration (n = 53; 37 women, 16 men), aged 17-88 years were recruited from our SE registry. According to their response time to intravenous administration of diazepam, patients were divided into four subgroups: Group I response times ranged from 20 to 60 s, group II from 61 to 120 s, group III from 121-180 s, and group IV from 181 to 360 s. The duration of SE was 10.76 +/- 3.46 h in the first group and 27.00 +/- 12.57 h in the last group. According to the etiology, patients with central nervous system tumors and metabolic disorders were the fastest responders, whereas those with cerebrovascular diseases and withdrawal of antiepileptic drugs were the slowest responders. This study revealed a positive correlation between the response time to diazepam administration and seizure duration during status epilepticus. Response time may have a role in predicting outcome of status epilepticus treatment, in particular, the effects of diazepam. Thus, longer-duration EEGs are indicated. (C) 2011 Elsevier GmbH. All rights reserved.
Keywords: Status epilepticus (SE); EEG analysis; Intravenous diazepam; Response time; RATS; EPILEPSY; CHILDREN